Poly(pseudo)rotaxane-like network mediated by hydrogen bonds in the solid-state structure of 1,7-phenanthroline - Arora, KK; Pedireddi, VR (Crystal Growth & Design, 2005)
A unique poly(pseudo)rotaxane-like network constituted by C-H center dot center dot center dot N hydrogen bonds in the solid-state structure of 1,7-phenanthroline and a self-inclusion host-guest type assembly in its salt form have been discussed. The assemblies are characterized by single-crystal X-ray diffraction methods.